(untitled) (Tokyo, Japan, 1970)
This book focuses its attention on one of the crurcial sectors in the economic development of Asia, discussing pass and current trends in agricultural development, problem areas in the production of particular crops, and the development of agriculture-related industries in the developing member nations of the Asian Development Bank.
Keywords: Văn minh, hiện đại,Technology and civilization,Civilization, Modern,Văn minh và công nghệ; Hội nghị,Congresses,Congresses,Hội nghị; 1950-,1950-